1998
DOI: 10.1046/j.1440-1711.1998.00757.x
|View full text |Cite
|
Sign up to set email alerts
|

Cytokines: Principles and prospects

Abstract: Summary Cytokines participate in the induction and eector phases of all immune and in¯ammatory responses. They are therefore obvious tools and targets for strategies designed to promote, inhibit or redirect these responses. However, the complexity of the cytokine network has hindered the widespread clinical application of many cytokines and it has become clear that a deeper understanding of the normal operation of this system in health and disease is needed for the therapeutic potential of cytokines to be full… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
100
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(101 citation statements)
references
References 197 publications
(334 reference statements)
0
100
1
Order By: Relevance
“…The expression of cytokines is regulated by intracellular signaling molecule in mammals [64]. Jonge and Ulloa [65] suggested that NF-kB plays a key role in regulating gene expression of inflammatory cytokines in immune cells.…”
Section: Valine Regulated Nf-kb P65 Ikba and Tor Genes Expression Inmentioning
confidence: 99%
“…The expression of cytokines is regulated by intracellular signaling molecule in mammals [64]. Jonge and Ulloa [65] suggested that NF-kB plays a key role in regulating gene expression of inflammatory cytokines in immune cells.…”
Section: Valine Regulated Nf-kb P65 Ikba and Tor Genes Expression Inmentioning
confidence: 99%
“…In mammals, production of cytokine can be modulated by the intracellular signalling molecules [56]. Signaling molecules NF-kB [57] and TOR [58] are critical factors mediating expression of cytokines in animals.…”
Section: Tablementioning
confidence: 99%
“…It may be noted that most of these cytokines as well as their soluble receptors (among them IL-6, IL-8, M-CSF, VEGF, sIL-2R␣, TNF receptors), are involved in normal and pathological wound healing and repair of tissue damage. 1,15,49 The concept of malignancies as "non-healing wounds," recently revoked, 15,50 implies, based on ample evidences, that several cytokines and growth factors released into the tumor microenvironment during interactions between tumor, stromal and immune cells may promote tumor development through auto-and paracrine enhancement of tumor cell proliferation, inhibition of apoptosis and facilitation of invasion. 15,51 Moreover, recent studies have pointed to the critical role of enhanced expression of some che- mokine receptors on human breast and melanoma tumor cells 16 in the formation and localization of distant metastases.…”
Section: Cytokine Serum Levels During Follow-upmentioning
confidence: 99%